Analisis Pemanfaaaatan Sistem Informasi Kepegawaian Pada MaManajemen Kepegawaian: Studi Kasus Pada STEI Hamfara Yogyakarta - Wijiharta Wijiharta (Kopertais Wilayah III Yogyakarta, 2018)
The study aims to determine the utilization of staffing information system to staffing management on Sekolah Tinggi Ekonomi Islam (STEI) Hamfara Yogyakarta. This study is descriptive qualitative using triangulation. The result of this study is the Sistem Informasi Kepegawaian (Simpeg) at STEI Hamfara has been used well in terms related to the foundation of planning and analysis (organizational) and in terms of giving kompenasi (ujrah). Simpeg utilized sufficiently in the quality of employees. Simpeg has not been ulitized optimally in terms of employee planning, staffing organization, employee development and employment relationship.